IbM KELOMPOK PEMBUDIDAYA IKAN PADA DAERAH TERTINGGAL KABUPATEN BOJONEGORO DALAM BENTUK DIVERSIFIKASI PRODUK OLAHAN BERKUALITAS FISH CAKE YANG DIPERKAYA RUMPUT LAUT [IbM OF FISH FARMER COMMUNITIES AT LACK AREA OF BOJONEGORO REGENCY THROUGH PRODUCT DIVERSIFICATION HAVE A CERTAIN QUALITY OF FISH CAKE WITH SEAWEED COMPLEMENTATION] - Moch. Amin Alamsjah (Jurnal Ilmiah Perikanan dan Kelautan, 2011)
Abstract IbM of Fish Farmer at Lack Area of Bojonegoro Regency Through Product Diversification Have a Certain Quality of Fish Cake With Seaweed Complementation (Moch. Amin Alamsjah dan Imam Suprayogi, 2011). Public service program through product diversification of fish cake from catfish with seaweed complementation for increasing of protein and iodine at lack of nutrient and disaster area of Bojonegoro Regency were done and developed by catfish farmer at Bojonegoro Regency so that it can inovate economic endeavor significantly. Response, enthuasiastic and activity of catfish farmer communities to expand diversification of catfish product with seaweed complementation were very high. Technique guidance and monitor programs must be expanded and dessiminated continuosly by Fisheries and Animal Husbandry Department and Trading and Industry Department of Bojonegoro Regency. Furthermore, networking between industry and market shall be facilitied by related institution so that catfish farmer can produce catfish flesh with seaweed complementation more better in quality and professional.